Diplomasi Publik Jepang (Studi Kasus : Budaya Pop Jepang Di Indonesia) - Kumalaningsih, Ratna Dewi; Hartati, Anna Yulia (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2022)
This thesis aims to discuss the importance of using Japanese pop culture in this case, Manga, Anime and Cosplay as part of Japanese public diplomacy in Indonesia. This discussion is divided into the MOFA (Japan Ministry of Foreign Affairs) program and the Japan Foundation as one of the actors who also carry out public diplomacy. The research in this thesis uses qualitative research methods with descriptive elaboration through the description of programs implemented such as the International Manga Award, World Cosplay Summit or even the appointment of anime or manga characters as Ambassadors (ambassadors) such as Doraemon as Anime ambassadors, the appointment of Kawaii Ambassadors and also The Cool Japan program is a program carried out to export pop culture and other commodities and content from Japan. This is intended to increase understanding and trust in Japan both in terms of politics between Indonesia and Japan, the economy and even a strategy to increase Japan's domestic tourism. From a political point of view, it can be seen through diplomatic relations with Indonesia which have existed for 60 years, and from an economic point of view between the two countries through the policy of granting broadcasting rights and licenses as well as expansion of investment by Japan which is expected to improve domestic welfare in Japan. tourism, namely increasing tourist visits to Japanese tourism which is now starting to be polished with a touch of pop culture elements such as Tokyo One Piece Tower, a theme park with the theme of the One Piece anime. So it can be said that Japanese pop culture is important for Japanese public diplomacy as a way to increase public trust and understanding outside Japan in general and especially the public in Indonesia regarding the image of Japan and gain prosperity for the Japanese domestic public.